The missing pieces of the HCV entry puzzle - Ogden, Sarah C (Future Virol, 2015)
The past decade has witnessed steady and rapid progress in HCV research, which has led to the recent breakthrough in therapies against this significant human pathogen. Yet a deeper understanding of the life cycle of the virus is required to develop more affordable treatments and to advance vaccine design. HCV entry presents both a challenge for scientific research and an opportunity for alternative intervention approaches, owning to its highly complex nature and the myriad of players involved. More than half a dozen cellular proteins are implicated in HCV entry; and a more definitive picture regarding the structures of the glycoproteins is emerging. A role of apolipoproteins in HCV entry has also been established. Still, major questions remain, and the answers to these, which we summarize in this review, will hopefully close the gaps in our understanding and complete the puzzle that is HCV entry.